Virtual Screening, ADMET Evaluation, and Molecular Docking Approach in the Discovery of Novel Potential Sweetening Agent - Yuniarta, Tegar Achsendo; Kesuma, Dini; Putra, Purnawan Pontana (Fakultas Farmasi, Universitas Surabaya, 2025)
This study presents a comprehensive in silico approach aimed at discovering novel artificial sweetener candidates through an integration of shape-based virtual screening, taste classification, ADMET evaluation, homology modeling, and molecular docking. Using saccharin as a template, compounds were screened from a large high-throughput database employing vROCS software, followed by taste prediction via VirtualTaste and Virtuous Sweet/Bitter. Two promising candidates were identified with Compound 1 exhibiting superior binding affinity against a homology-modeled human T1R2-T1R3 receptor, as evidenced by its docking score of –77.81 kcal/mol. ADMET analysis further revealed favorable pharmacokinetic properties for the compounds, suggesting their potential as safer non-caloric sweeteners. The integrative strategy not only streamlines candidate selection but also underlines the utility of molecular modeling in food science. Nevertheless, experimental validation and sensory evaluation are needed to confirm these findings and establish the compounds’ efficacy and safety profiles. These promising results encourage further in vitro and in vivo studies.